Neuroprotection by anaesthetics in rodent models of traumatic brain injury: a systematic review and network meta-analysis. (December 2018) - Archer, D.P.; McCann, S.K.; Walker, A.M.; Premji, Z.A.; Rogan, K.J.; Hutton, M.J.H.; Gray, L.J.
Abstract: Background: Anaesthetic neuroprotection in the setting of traumatic brain injury (TBI) remains unproved and is based upon the results in preclinical experiments. Here, we sought to synthesise the results in rodent models of TBI, and to evaluate the effects of publication bias, experimental manipulation, and poor study quality on the effect estimates. Methods: After a systematic review, we used pairwise meta-analysis to estimate the effect of anaesthetics, opioids, and sedative–hypnotics on neurological outcome, and network meta-analysis to compare their relative efficacy. We sought evidence of bias related to selective publication, experimental manipulation, and study quality. Results: Sixteen studies, involving 32 comparisons, were included (546 animals). The treatment improved the neurological outcomes by 35%; 95% confidence interval: 26–44%; P <0.001. The statistical heterogeneity was small (12%), but the 95% prediction interval for the estimate was wide (15–56%). The statistical power was low: 61% (90% confidence interval: 22–86%). The small sample size in the studies was a serious shortcoming reducing the statistical heterogeneity and obscuring differences in outcome between drugs and between experimental conditions. Conclusions: Anaesthetics do provide neuroprotection in rodent models of TBI. The effect-size estimates do not appear to be exaggerated by selective publication, experimental manipulation, or study design. The main shortcoming of the included studies were small sample sizes leading to low power and imprecision, which precluded the network meta-analysis from providing a meaningful ranking for efficacy amongst the drugs. Reliable preclinical investigations of neuroprotection by anaesthetics will require larger sample sizes.